Cardiovascular health in young adulthood and structural brain MRI in midlife: The CARDIA study. (15th August 2017) - Bancks, Michael P.; Allen, Norrina B.; Dubey, Prachi; Launer, Lenore J.; Lloyd-Jones, Donald M.; Reis, Jared P.; Sidney, Stephen; Yano, Yuichiro; Schreiner, Pamela J.
Abstract : Objective: To examine the association between the American Heart Association (AHA) Life's Simple 7 (LS7) metric and brain structure. Methods: We determined cardiovascular health (CVH) according to the AHA LS7, assigning 0, 1, or 2 points for meeting poor, intermediate, or ideal criteria for the 7 components (range 0–14) at baseline (aged 18–30 years in 1985–1986) and year 25 follow-up examination for 518 participants of the Coronary Artery Risk Development in Young Adults (CARDIA) brain MRI substudy. Visit-based CVH score and average score was assessed in relation to percent of intracranial volume of normal tissue of the whole brain, gray matter, and white matter, and abnormal tissue volume of white matter at year 25 using multivariable linear, logistic, and quantile regression, after adjustment for age, sex, race, field center, educational attainment, and alcohol consumption. Results: Mean percentage of whole brain volume, normal gray matter, and normal white matter was 81.3% (±2.5), 42.9% (±2.0), and 38.4% (±2.0). Greater CVH score at baseline (per each additional point at year 0: 0.1%, 95% confidence limits 0.01–0.3; p < 0.05) and average CVH score were associated with greater percentage of whole brain volume (per each additional point in average score: 0.2%, 95% confidence limits 0.04–0.3; p < 0.05). Visit-based or average CVH score was not significantly associated with normal gray or white matter volume or abnormal white matter volume. Conclusions: Maintaining ideal levels of cardiovascular health, determined by the LS7, in young adulthood is associated with greater whole brain volume in middle age but not regional differences in structure.